Synthese von(±)-cis- und (±)-trans-3-Methoxy-α-jonon; ein weiterer experimenteller Beitrag zur Chiralität des natürlichen (+)-Xanthophylls (Luteins) - R. Buchecker; P. Hamm; C.H. Eugster (CHIMIA)
The chirality of natural (+)-xanthophyll (lutein) has again been shown by chemical correlation with synthetic 3-methoxy-α-ionones of established stereochemistry to be (3 R, 3'R, 6'R).